Neural correlates of effort-dependent and effort-independent cognitive fatigue components in patients with multiple sclerosis. (February 2019) - Spiteri, Stefan; Hassa, Thomas; Claros-Salinas, Dolores; Dettmers, Christian; Schoenfeld, Mircea Ariel
Background: Among patients with multiple sclerosis (MS), fatigue is the most commonly reported symptom. It can be subdivided into an effort-dependent (fatigability) and an effort-independent component (trait-fatigue). Objective: The objective was to disentangle activity changes associated with effort-independent "trait-fatigue" from those associated with effort-dependent fatigability in MS patients. Methods: This study employed behavioral measures and functional magnetic imaging to investigate neural changes in MS patients associated with fatigue. A total of 40 MS patients and 22 age-matched healthy controls performed in a fatigue-inducing N -back task. Effort-independent fatigue was assessed using the Fatigue Scale of Motor and Cognition (FSMC) questionnaire. Results: Effort-independent fatigue was observed to be reflected by activity increases in fronto-striatal-subcortical networks primarily involved in the maintenance of homeostatic processes and in motor and cognitive control. Effort-dependent fatigue (fatigability) leads to activity decreases in attention-related cortical and subcortical networks. Conclusion: These results indicate that effort-independent (fatigue) and effort-dependent fatigue (fatigability) in MS patients have functionally related but fundamentally different neural correlates. Fatigue in MS as a general phenomenon is reflected by complex interactions of activity increases in control networks (effort-independent component) and activity reductions in executive networks (effort-dependent component) of brain areas.